PELATIHAN TERAPI MASSAGE PADA ANAK CEREBRAL PALSY UNTUK MELATIH KEMAMPUAN MENELAN DAN BICARA - Salis Qurrata Ayunin; Alvina Febrianti; Alliza Sheva Aulia; Nuraini Nuraini; Neny Widyana (ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
Children with cerebral palsy (CP) often experience oromotor dysfunction, leading to difficulties in swallowing and speech, which can affect nutrition, communication, and social interaction. This community service activity aimed to enhance the knowledge and skills of parents, caregivers, and educators in applying oromotor massage therapy to support swallowing and speech abilities in children with CP. The activity was conducted at Politeknik Al Islam Bandung on January 7, 2026, involving 25 participants. The methods included interactive lectures, demonstrations, simulations, supervised practice, and discussion sessions, accompanied by pre-test and post-test assessments. The results showed a significant increase in participants’ understanding and ability to perform oromotor massage correctly, including proper techniques for facial, lip, tongue, jaw, and pharyngeal stimulation. Participants also gained practical experience in adjusting techniques according to each child’s condition. The findings indicate that structured, repetitive, and guided oromotor massage can effectively improve swallowing and speech functions while empowering families to play an active role in home-based rehabilitation. The study concludes that this intervention is feasible, practical, and beneficial, and it is recommended that such training be regularly implemented and integrated into daily routines to optimize children’s functional outcomes. Keywords: cerebral palsy; oromotor massage; swallowing; speech; family empowerment